2013
DOI: 10.1111/pace.12102
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Postoperative Atrial Fibrillation Following Cardiac Transplantation: The Significance of Autonomic Denervation

Abstract: Risk of postoperative AF is significantly lower with OHT as in comparison to surgical maze. As both surgeries entail isolation of the pulmonary veins but only OHT causes disruption of autonomic innervation, this observation supports a mechanistic role of autonomic nervous system in AF. The benefit of targeting the cardiac autonomic system to treat AF needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
(104 reference statements)
0
17
0
1
Order By: Relevance
“…Consistently, the OHT group had uncommon AT (4.6 % AF + 2.9 % AFL) when compared with the two other thoracic surgeries (18.9 % AF + 7.4 % AFL and 19.8 % AF + 3.8 % AFL, respectively). In a similar study, Noheria et al 7 also found that POAF occurred only in 6.5 % of OHT patients, and was much more frequent after maze (22.7 %) or CBAG (16.4 %) surgery. POAF is usually benign and thought to be secondary to the immediate post-operative inflammatory state.…”
Section: Supraventricular Tachycardiamentioning
confidence: 66%
See 1 more Smart Citation
“…Consistently, the OHT group had uncommon AT (4.6 % AF + 2.9 % AFL) when compared with the two other thoracic surgeries (18.9 % AF + 7.4 % AFL and 19.8 % AF + 3.8 % AFL, respectively). In a similar study, Noheria et al 7 also found that POAF occurred only in 6.5 % of OHT patients, and was much more frequent after maze (22.7 %) or CBAG (16.4 %) surgery. POAF is usually benign and thought to be secondary to the immediate post-operative inflammatory state.…”
Section: Supraventricular Tachycardiamentioning
confidence: 66%
“…Moreover, AF episodes occurring long after transplantation are only associated with rejection or ischaemia, which alter the normal atrial substrate. 17 As expected, during the acute post-operative state, only denervation is likely to decrease AF in OHT patients, as suggested by the higher rates after maze 7 or double-lung transplantation 6 both of which require pulmonary vein isolation.…”
Section: Interesting Pathophysiological Findings Associated With Arrhmentioning
confidence: 74%
“…Conversely, blockade of the ganglion stellatum or renal sympathetic denervation should reduce the risk of ventricular arrhythmias in patients with prolonged-QT syndromes [7]. It is noteworthy in this context that extensive cardiac denervation, which may be present after orthotopic heart transplantation, is associated with a lower risk of supra ventricular rhythm disturbances, especially atrial fibrillation [8]. In these cases, the denervation should have protective effects and protect the myocardium from the autonomic imbalances of the extrinsic system before transmission.…”
Section: Extrinsic Systemmentioning
confidence: 99%
“…Part of the basis for this focus is the observation that in denervated hearts (such as after orthotopic heart transplant) there tends to be much less atrial fibrillation [68]. In turn, part of the theory behind which pulmonary vein isolation is an effective ablation technique for atrial fibrillation lies in that the act of isolating the pulmonary veins also leads to partial autonomic denervation.…”
Section: Clinical Correlatesmentioning
confidence: 99%